The myriapod fauna (Chilopoda, Diplopoda) of the Truong Sa (Spratly) archipelago, Vietnam - Son, Le Xuan; Dac, Le Xuan; Dung, Ngo Trung; Dung, Dinh The; Hung, Nguyen Duc; Anh, Nguyen Duc (Academia Journal of Biology, 2022)
This paper provides the first data on myriapods in the Truong Sa archipelago (Vietnam). A total of 292 myriapod specimens identified 9 species in 7 genera, 6 families, 5 orders of two classes Chilopoda and Diplopoda were collected from 10 islands in the Spratly archipelago of Khanh Hoa province in Vietnam including Southwest Cay (Song Tu Tay), Sand Cay (Son Ca), Namyit island (Nam Yet), Grierson Reef (Sinh Ton Dong), Sin Cowe island (Sinh Ton), Pearson Reef (Phan Vinh), Central Reef (Truong Sa Dong), Spratly island (Truong Sa), West Reef (Da Tay), and Amboyna Cay (An Bang), , , during two surveys in October–November 2020 and May–June 2021. The class Chilopoda has 276 specimens of seven species, 6 genera, 5 families in three orders (Scolopendromorpha, Geophilomorpha, and Lithobiomorpha); The class Diplopoda has 16 specimens of 2 species, 2 genera, and 2 families in two orders (Polydesmida and Spirobolida). Among the recorded species, Rhysida longipes (Newport, 1845) were commonly recorded on all islands.